Analisis Fraud Pentagon terhadap Kecurangan Laporan Keuangan (Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia pada Tahun 2011-2020) - Islamiati, Dian; Putra, Wahyu Manuhara (Universitas Batanghari Jambi, 2024)
This research aims to detect fraudulent financial reports using the fraud pentagon. The research uses elements in the form of financial targets, financial instability, number of independent commissioners, special party receivable transactions, special party debt transactions, special party sales transactions, special party purchase transactions, change of auditors, change of directors, and number of CEO photos. The sample in this research is 108 companies listed on the Indonesia Stock Exchange for the 2011-2020 period which were selected using a purposive sampling method. The sample companies in this study consisted of 54 fraud companies and 54 non-fraud companies. In testing the hypothesis using logistic regression analysis using the SPSS test tool. The results of this research show that financial targets and financial instability are not the driving factors for management to commit financial statement fraud, receivables transactions with privileged parties are a driving factor for fraud, but this is not the case for debt, sales and purchase transactions with privileged parties. Likewise, changing auditors in a particular financial year is also a driving factor for fraud, but not changing directors. Finally, the number of directors' photos in the annual report is not a driving factor in financial statement fraud.